Nanocarrier-Based Approaches for the Efficient Delivery of Anti-Tubercular Drugs and Vaccines for Management of Tuberculosis - Rajput, Amarjitsing; Mandlik, Satish; Pokharkar, Varsha (Frontiers in Pharmacology, 2021)
The faster spread of drug-resistant species of tuberculosis (TB) manifests as a severe infectious disease. It results in a dangerous threat to public health, thus demanding safe and more efficient therapies. Conventional drug therapy is challenging and frequently linked with adverse effects. Hence nanotherapeutics served as an emerging technique to overcome problems associated with current treatment. Nanotherapeutics helps to overcome toxicity and poor solubility issues of several drugs used in the management of tuberculosis. Due to their diameter and surface chemistry, nanocarriers encapsulated with antimicrobial drugs are readily taken up by macrophages, the main cells that host Mycobacterium tuberculosis. Macrophages play a crucial role at the site of infection as they serve as a carrier for drugs and are responsible for passive targeting tuberculosis. The surface of the nanocarriers is coated with ligands specific receptors, which further enhances drug concentration locally, hence the therapeutic potential of nanocarriers. This review highlights tuberculosis's current facts and figures, challenges associated with conventional treatment, different nano carrier-based systems, and application of nanocarriers in vaccine development.